Analysis of Science Laboratory Standardization in Practice Activities at Universitas Islam Negeri Fatmawati Sukarno Bengkulu - Elvi Yulianti; Pebby Udi Santika; Anggi Suwi Apriansyah; Ahmad Walid (UMSU, 2023)
This study aims to determine the completeness of science laboratory facilities and infrastructure, determine the intensity and implementation of science practicum, and determine the effect of laboratory facilities and infrastructure in supporting practicum activities at UINFAS BENGKULU. There are two types of data collection methods used in this research, namely primary data obtained directly from research subjects through the distribution of questionnaires that have been given and secondary data in the form of information collected through analysis in the form of interviews. The results in this study indicate that the carrying capacity of the science laboratory facilities and infrastructure at UINFAS BENGKULU indicates that the conditions have not met the minimum standard of 100%.